Pelaksanaan Bimbingan Dan Konseling Selama Pandemi di SMPN 6 Percut Sei Tuan - Amanda Putri Ramadhani T; Nurul Atika Roismaini Harahap; Abdurrahman Abdurrahman (JURNAL EDUKASI NONFORMAL, 2022)
This study aims to describe the implementation and implementation of Guidance and Counseling during a pandemic. The approach used is an approach with a descriptive method. The research subjects were Guidance and Counseling Teachers and Students of Class X and XI SMP Negeri 6 Percut Sei Tuan. Data collection techniques used are observation, interviews and documents. The results of the study explain that the implementation and services of BK are not effective. This ineffectiveness is caused by several obstacles and several factors. The main obstacle is the difficulty of communication between the counseling teacher and students because the counseling teacher and students cannot talk face to face or directly. This becomes an obstacle because BK teachers are very difficult to recognize and understand students only from social media. Of course, direct communication and on social media are very different. Other things that become obstacles include: decreased student enthusiasm, lack of student care for BK subjects, decreased immunity, ineffective time, BK teachers who have difficulty recognizing the character of their students, technology and media that are used incorrectly. and economic factors. The factors above have caused the implementation and implementation of Guidance and Counseling to not run effectively at SMP Negeri 6 Percut Sei Tuan.